Islam Kangean - Abdul Latief Bustami (Antropologi Indonesia, 2003)
This article is about Kangean's Islam. Islamic faith is present in cultural and historical society. Religion is interpreted and analyzed based on the cultural context of society. Therefore, there is a process of dialectics in religion as text and society as context. This process produces Islam which is different in different contexts. This article presents anthropological analysis and not theological analysis. Kangean Island has a culture which is different from Javanese, Bawean, and Maduranese culture. The religious faith is analyzed in the context of Kangean culture which results in Kangean's Islam. Kangean Island is shown in the ritual, numerology, belief in spirit, and poer of religious magic. In fact, Kangean's Islam responds variably to the various aspects mentioned above.